Boar spermadhesin AWN: novel insights in its binding behavior and localization on sperm. Issue 4 (8th January 2022) - Kroh, Pascal D; Braun, Beate C; Liu, Fan; Müller, Peter; Müller, Karin
Abstract: As a major spermadhesin first found in the seminal plasma (SP) of boars, AWN is described to fulfil a variety of reproduction related tasks. Although being the best investigated boar spermadhesin, information about its interaction with membranes is inconsistent. In this regard, previous reports locate AWN either inside or on the surface of sperm cells and at different regions, depending on the method and antibody used. Here, we localize native AWN (natAWN) in/on epididymal, ejaculated, capacitated, and acrosome-reacted boar sperm using epifluorescence and electron microscopy as well as an analysis of potential lipid-binding partners of natAWN and recombinant AWN (recAWN). By applying a custom-made anti-AWN antibody, localization of AWN in the equatorial segment (EQS) of ejaculated, capacitated, and acrosome-reacted boar sperm was discovered. Electron microscopy showed that AWN is localized both on the sperm surface and on the cytoplasmic side of the plasma membrane and in close vicinity to the nuclear and both acrosomal membranes of sperm. Analysis of epididymal sperm indicated migration of AWN from the retral postacrosomal part to the EQS during the epididymal passage. In contrast to hypotheses claiming a specific association of AWN to phosphatidylethanolamine (PE) and in line with our previous study describing an interaction with phosphatidic acid (PA), the current results show a rather electrostatically driven binding mechanism of AWN to negative lipids. In conclusion, this work provides new insights into the arrangement of AWN in the EQS, which suggest a possible role in sperm–oocyte fusion. Abstract : Spermadhesin AWN is highly associated with the equatorial segment of boar sperm, and its binding behavior is electrostatically driven.